The cost of security: Analyzing strategies to hedge hydrogen import disruption under stochastic representation of weather - Julian Keutz; Jan Kopp (Institute of Energy Economics at the University of Cologne (EWI), 2025)
The European Union's pursuit of climate neutrality necessitates a robust and secure energy system that will likely become reliant on imported green hydrogen. However, this dependency introduces inherent risks related to import disruptions and the weather-driven production variability of green hydrogen. This paper develops a comprehensive modeling approach to address these risks in a decarbonized European energy system. We use stochastic optimization to account for weather-induced variability, while applying dedicated mitigation strategies to analyze the cost and implications of hedging against import disruptions. We model hydrogen imports via long-term contracts, with prices and delivery profiles determined based on a stochastic calculation of the levelized cost of hydrogen supply. This approach informs the stochastic modeling of the European energy system using the HYEBRID model, which accounts for weather variability across domestic and exporting regions. Our analysis reveals that the stochastic extension of HYEBRID reduces system costs by one-third compared to a deterministic solution that assumes average weather conditions. We also identify the need for a substantial expansion of hydrogen storage capacity, considerably exceeding previous estimates, to manage fluctuations in both domestic and imported supply. a pure cost minimization of imports results in significant market concentration, with only three exporters being contracted. By evaluating strategies to mitigate import disruption risk, we find that diversification and import reduction strategies incur higher costs in the investment stage, which can be economically justified if the perceived risk of exporter disruption is sufficiently high.
Keywords: C61; F52; Q27; Q41; Q42; Q48; 330; Energy System Modeling; Hydrogen Infrastructure; Stochastic Optimization; Weather Variability; Hydrogen Import Risks